2020
DOI: 10.26719/2020.26.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and its associated factors among older people: a community-based study in Egypt

Abstract: Furthermore, it is associated with age-related diseases in older women such as osteoporosis and breast cancer (11). Lastly, quitting smoking tobacco is more difficult with advancing age due to significant and prolonged nicotine dependence (12). Although many studies have focused on tobacco use among adolescents and adults, the literature is lacking when examining tobacco use in older and retired people. This study aimed to estimate the prevalence and type of tobacco use among older people in Mansoura, Egypt. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
1
11
1
2
Order By: Relevance
“…Other studies in low-and middle-income countries (e.g., Egypt, Ghana, and Indonesia) have found tobacco use among older adults was associated with men and rural residence (Abdel-Hady & El-Gilany, 2020; Yawson et al, 2013;Pengpid & Peltzer, 2019). Apart from Ghana, the studies from China, Egypt, and Indonesia found tobacco use in older adults was associated with lower education (Abdel-Hady & El-Gilany, 2020;Pengpid & Peltzer, 2019;Yang et al, 2015). These findings suggest tobacco control strategies such as cessation that could specifically target older adults in low social and demographic positions.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies in low-and middle-income countries (e.g., Egypt, Ghana, and Indonesia) have found tobacco use among older adults was associated with men and rural residence (Abdel-Hady & El-Gilany, 2020; Yawson et al, 2013;Pengpid & Peltzer, 2019). Apart from Ghana, the studies from China, Egypt, and Indonesia found tobacco use in older adults was associated with lower education (Abdel-Hady & El-Gilany, 2020;Pengpid & Peltzer, 2019;Yang et al, 2015). These findings suggest tobacco control strategies such as cessation that could specifically target older adults in low social and demographic positions.…”
Section: Discussionmentioning
confidence: 97%
“…Contudo, passados 50 anos da publicação do primeiro documento governamental (37) acerca dos prejuízos do tabagismo à saúde, o mesmo fator de risco persiste acometendo a qualidade de vida mundialmente. Sabe-se que o tabagismo é motivado por uma complexa interação entre fatores ambientais, efeitos biológicos da nicotina e fatores sociais, em sua maioria difíceis de determinar, porém proporcionalmente associados ao sofrimento psicológico e a sintomas depressivos (23).…”
Section: Qualidade De Vida E Tabagismounclassified
“…Recente estudo realizado no Egito demonstrou que idosos do sexo masculino e analfabetos tiveram maior tendência a tornarem-se tabagistas, em parte por sua situação de vulnerabilidade socioeconômica, acarretando um estilo de vida menos saudável (23). Abordar esta face do vício é, por muitas vezes, dificultoso sem o estabelecimento de um vínculo prévio com o idoso, pois afeta a veracidade dos fatos referidos por ele no atendimento.…”
Section: /15unclassified
“…Research has documented that both smoking and using smokeless tobacco products (SLT) are the major risk factors of non-communicable diseases worldwide [ 2 , 4 ]. Among older adults, tobacco use has also been related to an increased risk of cognitive impairment, dementia, several sensory problems, loss of function, mobility, and independence [ 5 , 6 ]. Despite the well-established detrimental effects of tobacco use, we believe its use may have been increased during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of the COVID-19 pandemic reminded us how interconnected the world is and that COVID-19 knows of no border and affects people on both sides of the border, including those at refuge [ 5 ]. COVID-19 poses an increased threat to refugees and displaced persons as they live in densely populated camps, making social distancing, hand washing, and personal hygiene difficult to maintain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%